Libraries and Publishers Respond to Disaster with Groundbreaking Collaboration. - Moore, Mary; Burrows, Suzetta; Collins, Maria; Roderer, Nancy (Journal of Electronic Resources in Medical Libraries)
The earthquake in Haiti prompted significant response from both health care workers and health sciences libraries. Individual libraries in the United States and elsewhere struggled to provide relief workers with health information resources and services. This column describes the Haiti earthquake, the response of health care workers, one organization's experience in delivering services on the frontlines, the response of one library, and the Emergency Access Initiative (EAI), an effective solution to offering information resources in times of disaster, developed and implemented by the National Library of Medicine in association with health sciences publishers. Since the Haiti earthquake, the EAI has once again been activated in support of Pakistan.